Optimizing genetic diversity in Australian Holsteins and Jerseys: A comparative analysis of whole-genome and regional inbreeding depression effects - B.A. Scott; M. Haile-Mariam; F. Tiezzi; I. van den Berg; C. Maltecca; J.E. Pryce (Journal of Dairy Science)
ABSTRACT: Homozygosity, which can arise from several genetic mechanisms including inbreeding, is frequently observed in the offspring of related parents. This inbreeding can lead to a reduced performance, owing to a phenomenon known as inbreeding depression. This study assessed inbreeding depression using whole-genome and regional approaches in first-lactation Australian Holsteins and Jerseys, involving ∼33,000 Holstein and 7,000 Jersey cows born between 2000 and 2017. These cows had phenotypic records (milk production, fertility, and survival), pedigree records, and genomic data available. We analyzed genome-wide inbreeding depression through a mixed animal model examining 4 measures of inbreeding: pedigree data, runs of homozygosity (ROH) of at least 1 Mb, ROH greater than 8 Mb, and ROH exceeding 16 Mb, which indicates more recent inbreeding. Additionally, unique ROH haplotypes, identified using a sliding-window approach, were incorporated as fixed effects in the model to estimate their effect on the traits of interest. Results indicated that a 1% increase in pedigree inbreeding led to reduced performance across all traits, with estimates of inbreeding depression ranging from 0.11% to 0.45% of the phenotypic mean. In Holsteins, genome-wide estimates (FROH) were significant and reasonably aligned with pedigree estimates, whereas more recent inbreeding (FROH >16 Mb) had between 2.6 and 3.3 times greater effect on inbreeding depression across all traits compared with smaller FROH (≥1 Mb). In Jerseys, more recent inbreeding had a 2.2 to 2.3 times greater reduction in the performance of milk and protein yields for a 1% increase in genomic inbreeding. For both fitness traits in Jerseys, the effects of inbreeding on fertility and survival were not significant. The most negative effects of ROH were also noted in specific traits: Jersey and Holstein cows with unfavorable ROH took significantly longer to recalve and showed marked reductions in production traits. Moreover, increased homozygosity in certain genomic regions, such as BTA25 in Jerseys, markedly reduced performance, highlighting the importance of genomic location in assessing the effects of homozygosity. These data inform next-generation mating programs, emphasizing avoiding inbreeding in genomic regions most susceptible to inbreeding depression, to enhance animal performance.